Propuesta de producción más limpia para las plantas paneleras de Cundinamarca (2022)
The present investigation is based on the identification of the negative impacts generated by the production of panela in Cundinamarca and the activities that cause them; with the objective of proposing cleaner production strategies that mitigate said impacts, benefit the productivity of the sugar mills, and that additionally, are recognized through environmental certifications, such as the organic panela certificate that allows producers to make their way to the outside market.